2019
DOI: 10.1002/tbio.201900017
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence lifetime imaging for intraoperative cancer delineation in transoral robotic surgery

Abstract: This study evaluates the potential for fluorescence lifetime imaging (FLIm) to enhance intraoperative decisionmaking during roboticassisted surgery of oropharyngeal cancer. Using a custom built FLIm instrument integrated with the da Vinci robotic surgical platform, we first demonstrate that cancer in epithelial tissue diagnosed by histopathology can be differentiated from surrounding healthy epithelial tissue imaged in vivo prior to cancer resection and ex vivo on the excised specimen. Second, we study the flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 42 publications
0
50
0
Order By: Relevance
“…While this study focused on excised specimens, the long-term goal is to establish FLIm as an intraoperative tool scanning the surgical bed with a fiber optic. Recent studies from our group demonstrated the applicability of FLIm for in vivo applications [17,22,41]. The transition from ex vivo to in vivo settings will involve a few adaptations of the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this study focused on excised specimens, the long-term goal is to establish FLIm as an intraoperative tool scanning the surgical bed with a fiber optic. Recent studies from our group demonstrated the applicability of FLIm for in vivo applications [17,22,41]. The transition from ex vivo to in vivo settings will involve a few adaptations of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that FLIm images can be acquired either during surgery [17][18][19] or on excised specimens [10] to characterize biochemical features and associated pathologies. In particular, FLIm has been demonstrated to identify breast tumor regions [10,20], glioma tumors [21], oropharyngeal cancer [22] and atherosclerotic lesions [18]. In a recent study, the ability to identify breast tumors was demonstrated for small regions correlated visually with histology slides [10].…”
Section: Introductionmentioning
confidence: 99%
“…An additional technique for real-time identification of cancerous growth during transoral surgery makes use of fluorescence lifetime imaging (FLIM) observed through and intraoperative fluorescence spectroscopy. 23,24 This type of enhanced intraoperative visualization takes advantage of the autofluorescence capabilities of the tissues to distinguish malignant and premalignant tissues from surrounding tissues. Using a modified robotic arm containing a multimode fiberoptic, an excitation laser is delivered to the tissue region to induce autofluorescence of porphyrins, Nicotinamide adenine dinucleotide phosphate (NAD(P)H), and flavin adenine dinucleotide (FAD).…”
Section: Innovative Imaging Systems For Tlm and Torsmentioning
confidence: 99%
“…23,24 With this method, cancerous tissues can be identified without the application of exogenous probes and the re-sectioned sites can be intraoperatively examined for remaining tumors post-extraction. [23][24][25] Although FLIM can provide an effective means of detecting cancerous tissues based on changes in the molecular composition of cells, the study has found that several factors can affect this type of image guidance. Among the factors that could affect FLIM under TORS are tissue diversity, thickness of the epithelium, cancer cell type, removal method (leaser or electrocautery), and presence of bleeding.…”
Section: Innovative Imaging Systems For Tlm and Torsmentioning
confidence: 99%
See 1 more Smart Citation